Identitas Garuda Indonesia dalam Rubrik Garuda Indonesia News Majalah Colors 2016 - Holy R Dhona (Atma Jaya Indonesia Catholic University, Jakarta, 2017)
There is no place for in-flight magazine in the heart of Indonesian communication research. As an airline miscellaneous, communication scholars often did not see it as an instrument of corporate communication that laden with corporate identity. Inquiring the Garuda Indonesia News rubric in Colors in-flight magazine, this study focus on how the identity of Garuda Indonesia circulated on the texts. Using quantitative content analysis on how the corporate was represented on the texts, this study argue that Garuda Indonesia identified as national-level corporate rather than international-level corporate. This study suggests contextualizing the concept of a corporate identity rather than apply it as a taken-grated formulation or stages.